PENGARUH PENGGUNAAN LKS MENGINTEGRASIKAN STRATEGI REACT DALAM PEMBELAJARAN KONTEKSTUAL TERHADAP KOMPETENSI IPA SISWA KELAS VII SMPN 29 PADANG - Marlina Alimir; Asrizal Asrizal; Letmi Dwiridal (Universitas Negeri Padang, 2017)
Science is an important subject in school learning. Science can improve students' thinking skills to solve problems in daily life. Base on the reason, students should be understand science well. The real condition shows that students' science compatence is low. One solution of this problem is to use interesting teaching materials which is related to daily life. The purpose of the research is to investigate the influence of implementation of student worksheet by integrating REACT strategy in contextual learning toward student competence of grade VII SMPN 29 Padang. Type of research is a quasi experiment with randomized control only design. The research population was all students of grade VII SMPN 29 Padang that registered in academic year 2016/2017. Sampling technique was purposive sampling. The sample of the population consist of 34 students in the experimental class and 33 students in the control class. Instruments research consist of three parts namely learning result test sheet for knowledge, observation sheet for attitude, and performance assesment sheet for skill competence of students. Data were analyzed by descriptive statistical analysis, normality and homogeneity test, and comparison of two means test. Based on the result of data analysis can be stated that student worksheet by integrating strategy REACT in contextual learning gives significant effect toward students competencies at 95% significant level